Commercialization of Swedish Patents: A Pilot Study in the Medical and Hygiene Sector - Roger Svensson (The Research Institute of Industrial Economics (IUI), 2002)
In this paper, I analyze the commercialization of patents in the Swedish medicine & hygiene sector. A unique database makes it possible to use a new method, where I follow the commercialization process of individual patents. A surprisingly low share (10%) of the inventions was discovered at universities or in firms close to universities, although 1/3 of total R&D is undertaken at universities in Sweden. The commercialization rate is higher among small firms and entrepreneurs compared to medium-sized and large firms, but the success rate is lower for the former groups. With respect to mode of commercialization, 90% of the patents are commercialized in existing firms and only 10% in new start-ups. Few patents are sold or licensed abroad, and even then, manufacturing of the invention often takes place in Sweden. It seems like there is a lack of external venture capital to a higher degree in the commercialization phase than in the R&D phase. Entrepreneurs and small firms often claim that financing and difficulties to find a firm willing to manufacture the invention are the largest problems during the commercialization, or the main reasons why the patent was not commercialized. The reasons why larger firms do not commercialize their patents are that they often give priority to other inventions
Keywords: M13; O32; 330; Patents; R&D; Commercialization; Financing; Entrepreneurship; Patent; Industrielle Forschung; Forschungsfinanzierung; Medizintechnische Industrie; Schweden